KESENIAN BATAMBUA SAMPAI AMA PADA MASYARAKAT TANJUNG ALAI KOTO MALINTANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Boy MJ Saputra; Wimbrayardi Wimbrayardi; Syahrel Syahrel (SENDRATASIK UNP, 2013)
Absract   This examine be witching to description and to know how presentation “Tambua” till discase-germ of pupil Tanjung Alai Koto Malintang a district of Tanjung Raya. The regent Of Agam. The theory that are using is curve theory and presentasion, kind of examine are qualitative with collective technich, analysis data with classification data primer and scundare. The result of examine are : 1.) all the players are men. 2.) meansof music are 13 Tambua, 1 Tassa and 1 Pupuik Batang Padi. 3.) The song that they wild play is Siaman Tagagau. 4.) The uniform that they are wearing is Galembong and destar. 5.) The place is in Tanjung Alai. 6.) The aundiences are people around Tanjung Alai Koto Malintang and all invitation.   Kata kunci : bentuk, penyajian, kesenian, Ama